Improving PICC use and outcomes in hospitalised patients: an interrupted time series study using MAGIC criteria. Issue 4 (13th November 2017) - Swaminathan, Lakshmi; Flanders, Scott; Rogers, Mary; Calleja, Yvonne; Snyder, Ashley; Thyagarajan, Rama; Bercea, Priscila; Chopra, Vineet
Abstract : Background: Although important in clinical care, reports of inappropriate peripherally inserted central catheter (PICC) use are growing. Objective: To test whether implementation of the Michigan Appropriateness Guide for Intravenous Catheters (MAGIC) can improve PICC use and patient outcomes. Design: Quasi-experimental, interrupted time series design at one study site with nine contemporaneous external controls. Setting: Ten hospitals participating in a state-wide quality collaborative from 1 August 2014 to 31 July 2016. Patients: 963 hospitalised patients who received a PICC at the study site vs 6613 patients at nine control sites. Intervention: A multimodal intervention (tool, training, electronic changes, education) derived from MAGIC. Measurements: Appropriateness of PICC use and rates of PICC-associated complications. Segmented Poisson regression was used for analyses. Results: Absolute rates of inappropriate PICC use decreased substantially at the study site versus controls (91.3% to 65.3% (−26.0%) vs 72.2% to 69.6% (−2.6%); P<0.001). After adjusting for underlying trends and patient characteristics, however, a marginally significant 13.8% decrease in inappropriate PICC use occurred at the study site (incidence rate ratio 0.86 (95% CI 0.74 to 0.99; P=0.048)); no change was observed at control sites. While the incidence of all PICC complications decreased to a greater extent at the study site, the absolute difference between controls and intervention was small (33.9% to 26.7% (−7.2%) vs 22.4% to 20.8% (−1.6%); P=0.036). Limitations: Non-randomised design limits inference; the most effective component of the multimodal intervention is unknown; effects following implementation were modest. Conclusions: In a multihospital quality improvement project, implementation of MAGIC improved PICC appropriateness and reduced complications to a modest extent. Given the size and resources required for this study, future work should consider cost-to-benefit ratio of similar approaches.